Musical analyses and musical exegesis : the shepherd's melody in Richard Wagner's Tristan and Isolde /: the shepherd's melody in Richard Wagner's Tristan and Isolde. (2021) - Nattiez, Jean-Jacques, 1945-
No abstract available